L’adoption du Contrôle de Gestion à l'Hôpital Marocain : Explication par l'approche PLS - Boussetta Mohamed; Alami Saad (European Scientific Journal, ESJ, 2017)
For many authors the adoption of management control by companies is justified by the positive correlation between the implementation of this system and the increase of the organizational performance of the company. In Morocco, a single study focused on understanding the determinants of the choice of implementation of management control in the Moroccan context (Ahsina K., 2012), that is why we had the idea of developing a conceptual model adapted to Moroccan public hospitals. As a result, our problem is as follows: What is the impact of the determinants of management control on the organizational performance of the Moroccan public hospital ? This article presents, in a first point a review of the literature and the formulation of research hypotheses, in a second point the research methodology and in a last point the results of the descriptive analysis of the research.